Treasury supply shocks and the term structure of interest rates in the UK - Andras Lengyel (Magyar Nemzeti Bank, 2022)
How does the additional debt issued by the government affect the term structure of interest rates? In this paper we identify Treasury supply shocks using intraday high-frequency data, by exploiting the institutional setup of the UK government bond primary market. We find that supply shocks have positive effects on nominal and real interest rates. Most of the reaction is due to real term and inflation risk premia rather than the expectation component of yields. We argue both theoretically and empirically that supply shocks transmit via the repricing of duration and inflation risks in the economy. We also document that these effects are stronger under adverse economic and financial conditions.
Keywords: E43; E44; E60; 330; Term structure; government debt; bond risk premia; high-frequency identification